The flexible performer in interactive theatre: developing The Last Great Hunt's Pollyanna. Issue 2 (4th May 2018) - Ashford, Lawrence
Abstract : This article considers the demands of immersive, participatory, and interactive theatre, and the type of performer and performance training required to facilitate these. It provides an account of the development and performance of an interactive work that was inspired by the mechanics of video gaming, and that sought to give its audience control over the narrative and the way it was revealed. By framing performers as 'interfaces' rather than actors, audience interactions with the environment, the (loosely plotted) narrative, other audience members, and the performers themselves were able to be facilitated and incorporated into the world of the production. This dramaturgy demanded of the performers specific skill-sets. This article outlines the performance-making process of The Last Great Hunt theatre company in developing their work Pollyanna to show how each performance emerged through interaction with and within the audience, and arguing for a contemporary performer training that equips performers with skills in what Tim Fitzpatrick – developing the pioneering ethnomusicological work of Parry and Lord – calls 'flexible performance'.